320-row CT renal perfusion imaging in patients with aortic dissection: A preliminary study - Liu, D.; Liu J; Wen, Z.; Li, Y.; Sun, Zhonghua; Xu, Q.; Fan, Z. (Public Library of Science, 2017)
Objective: To investigate the clinical value of renal perfusion imaging in patients with aortic dissection (AD) using 320-row computed tomography (CT), and to determine the relationship between renal CT perfusion imaging and various factors of aortic dissection. Methods: Forty-three patients with AD who underwent 320-row CT renal perfusion before operation were prospectively enrolled in this study. Diagnosis of AD was confirmed by transthoracic echocardiography. Blood flow (BF) of bilateral renal perfusion was measured and analyzed. CT perfusion imaging signs of AD in relation to the type of AD, number of entry tears and the false lumen thrombus were observed and compared. Results: The BF values of patients with type A AD were significantly lower than those of patients with type B AD (P = 0.004). No significant difference was found in the BF between different numbers of intimal tears (P = 0.288), but BF values were significantly higher in cases with a false lumen without thrombus and renal arteries arising from the true lumen than in those with thrombus (P = 0.036). The BF values measured between the true lumen, false lumen and overriding groups were different (P = 0.02), with the true lumen group having the highest. Also, the difference in BF values between true lumen and false lumen groups was statistically significant (P = 0.016), while no statistical significance was found in the other two groups (P > 0.05). The larger the size of intimal entry tears, the greater the BF values (P = 0.044). Conclusions: This study shows a direct correlation between renal CT perfusion changes and AD, with the size, number of intimal tears, different types of AD, different renal artery origins and false lumen thrombosis, significantly affecting the perfusion values.